Photocatalytic Degradation Of Paracetamol On Nitrogen-Doped Carbon Dots / Titanium Dioxide Photocatalytic Membrane Under Visible Light Irradiation - Khor, Jia Xuan (2020)
Paracetamol is a common component contains in various analgesic medicines. It is often detected as a pharmaceutical waste in water sources due to its wide applications in the production of medicine. The removal of paracetamol from water sources is challenging due to its non-biodegradable property and low concentration in water bodies. Hence, this research was conducted to study the photocatalytic degradation of paracetamol by using hybrid nitrogen-doped carbon dots/titanium dioxide (N-CDs/TiO2) photocatalyst under visible light. To eliminate the recycling step of the hybrid photocatalyst, chemical grafting was employed to attach the hybrid photocatalyst on membrane surface to produce photocatalytic membrane. Firstly, hydrothermal technique was used to synthesize the N-CDs solution from oil palm fronds. The prepared N-CDs solution was incorporated with pure anatase phase TiO2 by using the ex-situ hydrothermal method in four different loadings of N-CDs (1, 2, 3 and 4 mL). The hybrid photocatalyst with 3 mL N-CDs loading showed the best photocatalytic degradation of paracetamol with an outstanding rate constant of 0.0187 min-1 . This hybrid photocatalyst was therefore chosen for the fabrication of photocatalytic membrane. To fabricate the photocatalytic membrane, different loadings (0.1, 0.2 and 0.3 wt%) of the hybrid photocatalyst were chemically grafted on polyethersulfone (PES) membrane with 1.0 wt% PVP by using polyacrylic acid (PAA) monomer, ethylene glycol (EG) as the cross-linker and potassium persulfate (PP) as the initiator. Based on the photocatalytic degradation study on paracetamol, photocatalytic membrane with the highest loading of hybrid photocatalyst (0.3 wt%) showed the best photocatalytic activity at a rate of 0.0028 min-1 . However, the permeability of photocatalytic membrane plunged due to the alteration of membrane morphology by the grafted PAA monomer. The synthesized photocatalysts were characterized by using X-ray diffraction (XRD) analysis, Fourier transform infrared (FTIR) spectrometer, zeta potential analysis, scanning electron microspocy (SEM) and energy dispersive X-ray (EDX) spectroscopy to study their crystallographic phases, functional groups, surface charges and morphologies respectively. Meanwhile, FTIR and SEM analyses were conducted to identify the functional groups and morphologies of the vi fabricated membranes. This study showed that by immobilizing 0.3 wt% of the synthesized hybrid photocatalyst with the optimum amount of 3 mL NCDs loading to PES membrane by using chemical grafting method, the fabricated photocatalytic membrane demonstrated great potential in the removal of paracetamol under the irradiation of visible light.